Handbook on advancements in smart antenna technologies for wireless networks - Sun, Chen, 1977-; Cheng, Jun, 1964-; Ohira, Takashi, 1955-; Books24x7, Inc. (Hershey : Information Science Reference, 2009)
'This book is a comprehensive reference source on smart antenna technologies featuring contributions with in-depth descriptions of terminologies, concepts, methods, and applications related to smart antennas in various wireless systems'--Provided by publisher.
Title from title screen.
Digitized and made available by: Books24x7.com.
Includes bibliographical references and index.
Text.
Available also in a print ed.
Mode of access: Internet via World Wide Web.
Keywords: Adaptive antennas -- Handbooks, manuals, etc; Radio -- Transmitters and transmission -- Handbooks, manuals, etc; Microwave antennas -- Handbooks, manuals, etc; Wireless communication systems -- Equipment and supplies -- Handbooks, manuals, etc; Electronic books; Electronic books